Metabolic Reprogramming Promotes Myogenesis During Aging - Belli, Roberta; Bonato, Agnese; De Angelis, Luciana; Mirabilii, Simone; Ricciardi, Maria Rosaria; Tafuri, Agostino; Molfino, Alessio; Gorini, Stefania; Leigheb, Massimiliano; Costelli, Paola; Caruso, Maurizia; Muscaritoli, Maurizio; et al. (Frontiers in Physiology, 2019)
Sarcopenia is the age-related progressive loss of skeletal muscle mass and strength finally leading to poor physical performance. Impaired myogenesis contributes to the pathogenesis of sarcopenia, while mitochondrial dysfunctions are thought to play a primary role in skeletal muscle loss during aging. Here we studied the link between myogenesis and metabolism. In particular, we analyzed the effect of the metabolic modulator trimetazidine (TMZ) on myogenesis in aging. We show that reprogramming the metabolism by TMZ treatment for 12 consecutive days stimulates myogenic gene expression in skeletal muscle of 22 months-old mice. Our data also reveal that TMZ increases the levels of mitochondrial proteins and stimulates the oxidative metabolism in aged muscles, this finding being in line with our previous observations in cachectic mice. Moreover, we show that, besides TMZ also other types of metabolic modulators (i.e. 5-Aminoimidazole-4-Carboxamide Ribofuranoside-AICAR) can stimulate differentiation of skeletal muscle progenitors in vitro. Overall, our results reveal that reprogramming the metabolism stimulates myogenesis while triggering mitochondrial proteins synthesis in vivo during aging. Together with the previously reported ability of TMZ to increase muscle strength in aged mice, these new data suggest an interesting non-invasive therapeutic strategy which could contribute to improving muscle quality and neuromuscular communication in the elderly, and counteracting sarcopenia.